2015
DOI: 10.1016/j.cellsig.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid receptor interacting protein (CRIP1a) attenuates CB1R signaling in neuronal cells

Abstract: CB1 cannabinoid receptors (CB1R) are one of the most abundantly expressed G protein coupled receptors (GPCR) in the CNS and regulate diverse neuronal functions. The identification of GPCR interacting proteins has provided additional insight into the fine-tuning and regulation of numerous GPCRs. The Cannabinoid Receptor Interacting Protein 1a (CRIP1a) binds to the distal carboxy terminus of CB1R, and has been shown to alter CB1R-mediated neuronal function [1]. The mechanisms by which CRIP1a regulates CB1R activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 35 publications
(58 reference statements)
2
56
0
Order By: Relevance
“…[ 35 S] GTPγS binding to activated Gαi/o proteins was performed on membranes prepared from the control and RGS2 knockdown cells using the procedure previously described (Blume et al, 2015). Briefly, cells were homogenized in cold hypotonic buffer (20 mM HEPES, pH 7.4, 10 mM KCl, 1.5 mM MgCl 2 , 1 mM EDTA, 1 mM EGTA, 1 mM dithiothreitol and the Protease Inhibitor Cocktail) followed by centrifugation at 1,000 × g for 10 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…[ 35 S] GTPγS binding to activated Gαi/o proteins was performed on membranes prepared from the control and RGS2 knockdown cells using the procedure previously described (Blume et al, 2015). Briefly, cells were homogenized in cold hypotonic buffer (20 mM HEPES, pH 7.4, 10 mM KCl, 1.5 mM MgCl 2 , 1 mM EDTA, 1 mM EGTA, 1 mM dithiothreitol and the Protease Inhibitor Cocktail) followed by centrifugation at 1,000 × g for 10 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Exogenous CRIP1a reversed CB 1 receptor-mediated tonic inhibition of Ca 2+ currents, whereas CRIP1b could not[11]. CRIP1a-knockdown clones in the model neuroblastoma N18TG2 cells exhibited enhanced ERK1/2 phosphorylation efficacy in response to CP55940 and displayed a leftward shift in CP55940-mediated inhibition of forskolin-stimulated cAMP accumulation [12,13]. CB 1 receptor-mediated G i3 and G o activation by CP55940 was attenuated by CRIP1a over-expression, but robustly enhanced in CRIP1a-knockdown clones.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, CP55940-mediated G i1 and G i2 activation was significant enhanced in cells over-expressing CRIP1a, but not inCRIP1a-knockdown clones [14]. These studies suggest that endogenous levels of CRIP1a modulate CB 1 receptor-mediated signal transduction by facilitating a G i/o subtype preference for G i1 and G i2 , accompanied by an overall suppression of G protein-mediated signaling in neuronal cells [12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…A recently published article by some of the coauthors of this paper showed that manipulation of CRIP 1a expression in N18TG2 cells modulated constitutive and agonist-stimulated extracellular signal-regulated kinase 1/2 phosphorylation by the CB 1 R, and that CB 1 R coupling to Ga o and Ga i 3 was attenuated, whereas coupling to Ga i 1 and 2 was enhanced, by overexpression of CRIP 1a (Blume et al, 2015).…”
Section: Note Added In Proofmentioning
confidence: 99%